Development of Bakastive Games in Stimulating The Concentration Ability of ADHD Children in Raudhatul Athfal, Penjaringan Utara District - Herbanin Radie, Fahmarisa; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study aims to develop Bakastif game products at the Raudhatul Athfal institution in Penjaringan District, North Jakarta in stimulating concentration skills for ADHD children. This study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research location was at Raudhatul Athfal, North Jakarta, involving four ADHD students from three Raudhatul Anfhal institutions as samples in the study. Data were obtained through interviews, observations, expert validation tests, feasibility and effectiveness tests in the field. The results of the study showed that teachers faced limitations in utilizing APE due to the lack of facilities that were in accordance with the conditions, needs and characteristics of ADHD children. The validation results by PAUD experts, learning media experts, and curriculum experts showed that this Bakastif game tool was feasible to use, with an average score of 84% (Very Feasible category). Implementation in three RAs showed that the Bakastif game tool was effective to use, with an effective standard of